Distribución, de esponjas esciafilas en la zona intermareal de Aramar (Luanco, Asturias) - Lombas, I. (Boletim de Ciencias Naturales IDEA, 1982)
The distribution of the Sponges in a sciophilous habitat constitute of several crevices and cornices of tbe intertidal area of Aramar beach (Luanco, Asturias, North of Spain). The abundance index and habitat preferences for each species are given. 20 species were found, 3 of tbem are Calcarea and 17 Demospongiaria. 2 Demospongiaria species (Dysidea avara and Oíígoceras collectrix) are first records in the Spanish Atlantic Coasts, and other 3 Demospongiaria species (Stelligera rígida, Antho involvens and Halichondria bowerbanki) are new records for the East síde of the Bay of Biscay.